Early Dynamics of Interleukin-6 in Cerebrospinal Fluid after Aneurysmal Subarachnoid Hemorrhage - Ďuriš, Kamil; Neuman, Eduard; Vybíhal, Václav; Juráň, Vilém; Gottwaldová, Jana; Kýr, Michal; Vašků, Anna; Smrčka, Martin (Journal of neurological surgery. Part A, Central European neurosurgery, 2018)
BACKGROUND:  Subarachnoid hemorrhage (SAH) is a severe condition associated with high mortality. Early brain injury (EBI) plays an important role in the pathophysiology of SAH, and inflammation is a major contributor to EBI. Inflammation is a widely studied topic in both experimental and clinical conditions; however, just a few clinical studies have focused primarily on the early inflammatory response after SAH, and detailed information about the association between the dynamics of early inflammatory response with main clinical characteristics is lacking. This study analyzes the early dynamics of inflammatory response after SAH and evaluates the possible associations between the markers of early inflammatory response and main clinical characteristics. PATIENTS AND METHODS:  A total of 47 patients with a diagnosis of aneurysmal SAH within the last 24 hours were enrolled in the study. All treatments, including treatment of aneurysm (surgery/coiling) and implantation of a drainage system (external ventricular drainage/lumbar catheter), were conducted in the same way as in other patients with this diagnosis. Blood and cerebrospinal fluid (CSF) samples were collected three times a day for 4 days. The dynamics of proinflammatory cytokines were assessed, and associations between levels of the proinflammatory cytokines interleukin (IL)-6, IL-1β, or tumor necrosis factor (TNF)α and main clinical characteristics were evaluated using linear mixed-effect models. RESULTS:  The CSF levels of IL-6 were massively increased initially after SAH (up to 72 hours) with an additional increase in later phases (after 72 hours), but there was high variability in IL-6 levels. A significant association was noted between the Glasgow Outcome Scale score and both overall levels of IL-6 (p = 0.0095) and their dynamics (p = 0.0208); the effect of the Hunt and Hess scale was borderline (p = 0.0887). No association was found between IL-6 levels and Fisher grade, modality of treatment (surgery, coiling, no treatment), and later development of cerebral vasospasm. Plasmatic levels of IL-6 increased slightly, but no significant association was found. The levels of IL-1β and TNFα were within the physiologic range in both CSF and plasma. CONCLUSIONS:  Early dynamics of IL-6 in CSF are associated with a patient́s outcome. But it is difficult to use IL-6 alone for outcome prediction due to its high variability. The question is whether the dynamics of IL-6 could be used in combination with other early markers associated with brain injury. More detailed research is required to answer this question.
Keywords: Interleukin-6; biologické markery; lidé; Middle Aged; Adult; subarachnoidální krvácení; Prognosis; prognóza; Intracranial Aneurysm; Female; Glasgow Outcome Scale; cytokiny; intrakraniální aneurysma; Humans; Predictive Value of Tests; interleukin-6; Inflammation; Tumor Necrosis Factor-alpha; zánět; Cytokines; Subarachnoid Hemorrhage; lidé středního věku; Biomarkers; mužské pohlaví; ženské pohlaví; drenáž; Glasgowská stupnice následků; Drainage; Male; Aged; dospělí; TNF-alfa; prediktivní hodnota testů; senioři